Population and size structure for the settlements of Mizuhopecten yessoensis in Peter the Great Bay (Japan Sea) - Ludmila G. Sedova; Dmitry А. Sokolenko (Известия ТИНРО)
Current state of the scallop Mizuhopecten yessoensis settlements in Peter the Great Bay (Japan Sea) is considered on the data of diving surveys conducted by RV Ubezhdenny in the coastal zone of Primorye with the depth up to 20 m in summer and fall seasons of 2000-2012. The materials were collected from 11,000 diving stations using standard methods. Total abundance and biomass of the species is assessed by the method of Voronoy diagram (similar to the method of Tissen polygons). At present, total number of the scallop is about 4 million individuals which occupy the area 50 km2. Non-commercial scallops prevail in the settlements of closed and semi-open bays, but the size groups of commercial value dominate in the settlements located in the open waters. For the whole surveyed area, the portion of scallops with the shell height < 100 mm is 29.7 %, 100-120 mm - 20.8 %, > 120 mm - 49.5 %.